Composite Materials of Epoxy Resin–W System for Radiation Shielding Against Gamma Radiation - A. A. Rotkovich; D. I. Tishkevich; S. A. German; A. A. Bondaruk; S. V. Leonchik; E. S. Dashkevich; V. M. Fedosyuk; A. V. Trukhanov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Сomposite materials based on the epoxy resin–W system with varying W content (0–80 %) were obtained using the method of chemical curing. Microstructural investigations of the samples showed that with increasing W content there is a more uniform distribution of grains in the epoxy resin matrix could be observed. Agglomeration of W grains is noted for samples with filler content up to 40 %. Statistical analysis of the grain size of the initial W powder revealed that the probable diameter of W grains is 475 nm. The values of effective and relative densities of the experimental samples were obtained using the Archimedes method. The effective density varied from 1.16 to 4.36 g/cm3 with W powder content rising. The relative density values received ranged from 91 to 94 %, indica ting that there were no significant defects in the samples. X-ray diffraction analysis showed the presence of vcc-W and WO2 phases, indicating the oxidation of W in the thin surface layer of the powder. Calculation in Phy-X/PSD software allowed to evaluate the gamma radiation shielding efficiency for the epoxy resin–W system composite materials in 0.8–2.5 MeV energy range. It was observed that samples with filler content of 60 and 80 % were the most suitable for radiation shielding. It was found that the addition of W powder to the epoxy matrix contributed to the reduction of half attenuation layer values by 3.5 times from 9.448 to 2.672 cm for samples with 0 and 80 % W content, respectively, for 1.25 MeV radiation energy. The obtained results demonstrate the high efficiency of the proposed composite materials for shielding gamma radiation, which makes them a perspective candidate for manufacturing radiation shields.